TRANSFER PRICING: AUDIT TENURE, TAX MINIMIZATION, AND DEBT COVENANT IN CONSUMER CYCLICALS COMPANIES - Restu Fadhilah; Mohamad Zulman Hakim; Desita Nur Afifah; Isma Aliyah; Carrisa Putri Jayusman (International Journal of Economics, Education, Law and Social Sciences (IJEELSC), 2026)
This study aims to examine the effect of Audit Tenure, Tax Minimization, and Debt Covenant on Transfer Pricing. The population in this study consisted of 167 companies with a sample of 19 companies and 76 company data sets. The sampling technique used was purposive sampling. The data used in this study are quantitative data and secondary data in the form of annual financial reports of consumer cyclicals companies listed on the Indonesia Stock Exchange for the period 2021 - 2024. The results of this study indicate that audit tenure has no effect on transfer pricing, tax minimization has an effect on transfer pricing, and debt covenants have on transfer pricing.